Analisis Ketidaksesuaian Status Barang Outbound di Gudang Cargo Distribution Center - Maulana, Andy; Wiguna, Esa Setia; Alvionita, Nabila; Sholihah, Sita Aniisah; Poncotoyo, Wahyu; Firmansyah, Iqbal (Institut Transportasi dan Logistik Trisakti, 2022)
PT X equips their warehouse with a system called the Warehouse Management System (WMS) to help manage every work process in the warehouse. In the operation of this WMS, there is a problem of discrepancies in the status of goods between the status of goods in the WMS and conditions in the field which causes workflows such as activities for Customs purposes to be hampered and the quality of company information decreases. The problem of discrepancies in the status of these goods needs to be mapped in a structured manner and the cause of this discrepancy in the status of goods is sought in order to improve the quality of the company's warehouse services so this research needs to be carried out. In this study, the Seven Tools method was used to identify the level of discrepancy and analyze what factors caused the discrepancy in the status of the goods. The results showed that the average percentage of item status discrepancies was 34.43% during April 2021 - June 2021. it was found that the Man, Method, and Machine factors were the main causes of the discrepancy in the status of the goods.